Teeth outside the jaw: Evolution and development of the toothed head clasper in chimaeras - Karly E. Cohen; Michael I. Coates; Gareth J. Fraser (Proceedings of the National Academy of Sciences, 2025)
Chimaeras ( Holocephali ) are an understudied group of mostly deep-ocean cartilaginous fishes ( Chondrichthyes ) with unique characteristics that distinguish them from their distant relatives, sharks, skates, and rays. Unlike sharks, chimaeras lack scales and do not have serially replacing rows of serrated teeth crowned with enameloid. Instead, they possess a fused dentition of dentine tooth plates. Additionally, male chimaeras develop an articulated cartilaginous facial appendage, the tenaculum, which is covered in an arcade of tooth-like structures. These extraoral teeth remain poorly understood, and their evolutionary origin is unclear. We investigate the development of the tenaculum and its teeth throughout the ontogeny of the Spotted Ratfish, Hydrolagus colliei , to assess homology and convergence between this novel craniofacial feature and oral jaws. Our study aims to 1) describe the development of the tenaculum, 2) assess tenaculum tooth development in comparison to oral teeth and denticles, and 3) characterize the genes and tissues responsible for tenaculum tooth emergence. We found that juvenile male chimaeras develop a full tenaculum before tooth development is complete and that only mature males possess a fully toothed tenaculum. These extraoral teeth emerge from within the tenaculum rather than from the surrounding epithelium. We integrate our developmental data with fossil evidence of the tenacular dentition from the Carboniferous holocephalan Helodus simplex . Our findings show that the tenaculum is closely associated with the upper jaw and that tenacular dentition resembles separate shark-like oral tooth whorls more than modified dermal denticles.